Improvement of formability of ultrafine-grained materials by post-SPD annealing - Saray, Onur; Purcek, G.; Karaman, I.; Maier, H. J. (Elsevier Science Sa, 2014)
Ultrafine-grained (UFG) IF-steel, as an example of an essentially single phase UFG microstructure, was annealed at different temperatures and time intervals in order to improve its formability by achieving a good strength-ductility-formability balance. In general, annealing increased the ductility and formability of UFG steel. Annealing at temperatures inside the recovery region caused a limited improvement in the formability of UFG steel due to the relief of internal energy without considerable grain coarsening. As the grain size increased to above 4 mu m by annealing at temperatures inside the partially recrystallization region, the formability of UFG steel in the uniform region increased considerably, and localized deformation with early necking changed to a homogeneous mode as revealed by increased uniform thinning and enlargement of the membrane straining regime. Further grain coarsening resulted in a slight increase in uniform elongation both in uniaxial and biaxial tests. The UFG microstructure reduced the roughness of the free surface of biaxially stretched samples by decreasing the non-uniform grain flow, which leads to the so-called orange peel effect. Annealing of UFG microstructure did not degrade this positive effect due to the formation of sharp recrystallization textures although the annealed microstructures have relatively coarse grains. It can be concluded that a good balance between strength and uniform formability without an orange-peel effect can be achieved in UFG microstructures by well-design annealing processes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ultrafine-grained materials; Formability; Annealing; Erichsen test